# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime } = \frac {\left (1+\cos \left (4 t \right )\right ) y}{4}-\frac {\left (1-\cos \left (4 t \right )\right ) y^{2}}{800}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t \left (y+1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t \sqrt {1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}\cos \left (t \right ) y+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sqrt {t}\, \sin \left (t \right ) y+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {2 t y}{t^{2}+1}+y^{\prime } = \frac {1}{t^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y+y^{\prime } = {\mathrm e}^{t} t
\] |
✓ |
✓ |
|
\[
{}t^{2} y+y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}t^{2} y+y^{\prime } = t^{2}
\] |
✓ |
✓ |
|
\[
{}\frac {t y}{t^{2}+1}+y^{\prime } = 1-\frac {t^{3} y}{t^{4}+1}
\] |
✓ |
✓ |
|
\[
{}\sqrt {t^{2}+1}\, y+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sqrt {t^{2}+1}\, y \,{\mathrm e}^{-t}+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sqrt {t^{2}+1}\, y \,{\mathrm e}^{-t}+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 t y = t
\] |
✓ |
✓ |
|
\[
{}t y+y^{\prime } = t +1
\] |
✓ |
✓ |
|
\[
{}y+y^{\prime } = \frac {1}{t^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 t y = 1
\] |
✓ |
✓ |
|
\[
{}t y+\left (t^{2}+1\right ) y^{\prime } = \left (t^{2}+1\right )^{{5}/{2}}
\] |
✓ |
✓ |
|
\[
{}4 t y+\left (t^{2}+1\right ) y^{\prime } = t
\] |
✓ |
✓ |
|
\[
{}y+y^{\prime } = \left \{\begin {array}{cc} 2 & 0\le t \le 1 \\ 0 & 1<t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}\left (t^{2}+1\right ) y^{\prime } = 1+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (t +1\right ) \left (y+1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1-t +y^{2}-t y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{3+t +y}
\] |
✓ |
✓ |
|
\[
{}\cos \left (y\right ) \sin \left (t \right ) y^{\prime } = \cos \left (t \right ) \sin \left (y\right )
\] |
✓ |
✓ |
|
\[
{}t^{2} \left (1+y^{2}\right )+2 y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 t}{y+t^{2} y}
\] |
✓ |
✓ |
|
\[
{}\sqrt {1+y^{2}}\, y^{\prime } = \frac {t y^{3}}{\sqrt {t^{2}+1}}
\] |
✗ |
✓ |
|
\[
{}y^{\prime } = \frac {3 t^{2}+4 t +2}{-2+2 y}
\] |
✓ |
✓ |
|
\[
{}\cos \left (y\right ) y^{\prime } = -\frac {t \sin \left (y\right )}{t^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = k \left (a -y\right ) \left (b -y\right )
\] |
✓ |
✓ |
|
\[
{}3 t y^{\prime } = \cos \left (t \right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 y}{t}+\frac {y^{2}}{t^{2}}
\] |
✓ |
✓ |
|
\[
{}t y^{\prime } = y+\sqrt {t^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}2 t y y^{\prime } = 3 y^{2}-t^{2}
\] |
✓ |
✓ |
|
\[
{}\left (t -\sqrt {t y}\right ) y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y+t}{t -y}
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{\frac {t}{y}} \left (y-t \right ) y^{\prime }+y \left (1+{\mathrm e}^{\frac {t}{y}}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {t +y+1}{t -y+3}
\] |
✓ |
✓ |
|
\[
{}1+t -2 y+\left (4 t -3 y-6\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t +2 y+3+\left (2 t +4 y-1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t \sin \left (y\right )+{\mathrm e}^{t} y^{3}+\left (t^{2} \cos \left (y\right )+3 \,{\mathrm e}^{t} y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+{\mathrm e}^{t y} \left (1+t y\right )+\left (1+{\mathrm e}^{t y} t^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sec \left (t \right ) \tan \left (t \right )+\sec \left (t \right )^{2} y+\left (\tan \left (t \right )+2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {y^{2}}{2}-2 \,{\mathrm e}^{t} y+\left (-{\mathrm e}^{t}+y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t y^{3}+3 t^{2} y^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t \cos \left (y\right )+3 t^{2} y+\left (2 t^{2}+2 y\right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}3 t^{2}+4 t y+\left (2 t^{2}+2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 t -2 \,{\mathrm e}^{t y} \sin \left (2 t \right )+{\mathrm e}^{t y} \cos \left (2 t \right ) y+\left (-3+{\mathrm e}^{t y} t \cos \left (2 t \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 t y+y^{2}+\left (t^{2}+t y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 t \left (y+1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{t}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2}+\cos \left (t \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+y+y^{2} \cos \left (t \right )
\] |
✗ |
✓ |
|
\[
{}y^{\prime } = t +y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{-t^{2}}+y^{2}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = {\mathrm e}^{-t^{2}}+y^{2}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = {\mathrm e}^{-t^{2}}+y^{2}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = y+{\mathrm e}^{-y}+{\mathrm e}^{-t}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = y^{3}+{\mathrm e}^{-5 t}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = {\mathrm e}^{\left (y-t \right )^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (4 y+{\mathrm e}^{-t^{2}}\right ) {\mathrm e}^{2 y}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = {\mathrm e}^{-t}+\ln \left (1+y^{2}\right )
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = \frac {\left (1+\cos \left (4 t \right )\right ) y}{4}-\frac {\left (1-\cos \left (4 t \right )\right ) y^{2}}{800}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t \left (y+1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t y^{a}
\] |
✗ |
✓ |
|
\[
{}y^{\prime } = t \sqrt {1-y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y+{\mathrm e}^{-y}+2 t
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = 1-t +y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {t^{2}+y^{2}}{1+t +y^{2}}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = {\mathrm e}^{t} y^{2}-2 y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = t y^{3}-y
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = x \left (1-x\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = -x \left (1-x\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = x^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+x y = 0
\] |
✓ |
✓ |
|
\[
{}x y^{2}+x +\left (y-x^{2} y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+y^{2}+\left (x^{2}+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 2 x y
\] |
✓ |
✓ |
|
\[
{}x y^{2}+x +\left (x^{2} y-y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sqrt {-x^{2}+1}+\sqrt {1-y^{2}}\, y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime }-1+y = 0
\] |
✓ |
✓ |
|
\[
{}\tan \left (x \right ) y^{\prime }-y = 1
\] |
✓ |
✓ |
|
\[
{}y+3+\cot \left (x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x}{y}
\] |
✓ |
✓ |
|
\[
{}x^{\prime } = 1-\sin \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = y^{2}
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) \cos \left (y\right )^{2}+\cos \left (x \right )^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sec \left (x \right ) \cos \left (y\right )^{2} = \cos \left (x \right ) \sin \left (y\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = x y \left (y^{\prime }-1\right )
\] |
✓ |
✓ |
|
\[
{}x y+\sqrt {x^{2}+1}\, y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y = x y+x^{2} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\tan \left (x \right ) \sin \left (x \right )^{2}+\cos \left (x \right )^{2} \cot \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+y y^{\prime }+x^{2} y y^{\prime }-1 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|